Implementing the Hello Talk Application to Teach Speaking Skills in Vocational High Schools - Basir, Amin; Khamdanah, Khamdanah; Umaemah, Amroh; Rizka, Haira (Qualitative and Quantitative Research Center, 2024)
The use of technology-based applications is an interesting innovation in education. The use of digital applications is important in vocational schools because it supports interactive learning, improves practical communication skills, and prepares students to face the technology-based world of work. This research aims to analyze the implementation and examine the students' and teachers' perceptions of the Hello Talk in teaching English speaking at vocational high schools. This research used qualitative descriptive methodology. The research instruments used observation and interviews to obtain the necessary data. Observation is used to find out the implementation of the Hello Talk application in teaching speaking. Interviews find out more about the perceptions of students and teachers about the use of the Hello Talk application in learning to speak. The respondents of this study were 96 students divided into three groups and 2 English teachers. The data analysis technique used the Miles and Huberman model. The results show that the implementation of the Hello Talk application effectively enhances students' engagement, enthusiasm, and speaking skills while also supporting teachers in planning and evaluating lessons. Its features, such as voice-to-text conversion and tandem partner interactions, improve pronunciation and fluency, emphasizing the need for proper guidance and digital literacy. Integrating digital tools into language teaching can foster a more engaging and interactive learning environment. This study contributes to providing insight for teachers in utilizing technology to create interactive and innovative learning. Concrete steps to integrate digital tools into the language curriculum must be accompanied by adequate infrastructure and training to optimize results.